A folding-shank gravity installed anchor and its hydrodynamic characteristics in water: Physical modelling. (15th December 2020) - Han, Congcong; Wang, Xu; Liu, Jun
Abstract: The light-weight gravity installed plate anchor (L-GIPLA) is a plate-shaped anchor for securing offshore floating structures, which is dynamically installed with the aid of a booster. Therefore, it is necessary to investigate the hydrodynamic characteristics of the hybrid anchor (L-GIPLA + booster) during free fall in water. Model tests are conducted in the present study to investigate the drag coefficient and directional stability of the L-GIPLA and the corresponding hybrid anchor. On the basis of model testing results, the geometry of the L-GIPLA is optimised with tapered fluke with round-grinded edge and folding shank. It is verified by model tests that the modified anchor with folding shank is favourable for improving the directional stability and reducing the drag coefficient for the hybrid anchor. In order to mitigate the effect of the mooring line on the directional stability of the hybrid anchor, an arched fin or fan-shaped plate is set at the rear of the hybrid anchor in the direction opposite the shank to balance the drag force on the mooring line. Highlights: The hydrodynamic characteristics of the hybrid anchor (L-GIPLA + booster) during free fall in water have been investigated. The geometry of the L-GIPLA is optimised with tapered fluke with round-grinded edge and folding shank. Effective measures are proposed to mitigate the tilt of gravity installed anchors during free fall in water.